Systematic Approach to Optimization for Protection Against Intentional Ultrashort Pulses Based on Multiconductor Modal Filters - Anton O. Belousov; Talgat R. Gazizov (Complexity)
The problem of protecting radio electronic equipment from ultrashort pulses is of utmost importance nowadays since conductive interference poses the biggest danger to its proper functioning. The article considers the issue of protecting equipment by means of modal filters (MFs) and analyzes the structures of multiconductor microstrip MFs. We present the results of a complex study of the possibility to conduct the optimization (both separate and simultaneous) of a multiconductor MF by different criteria and the formulation of the basic (electrical) optimization criteria for MF. We have formulated the amplitude and time criteria for optimizing an MF (with any number of conductors) in an analytical form and obtained a general multicriteria objective function for optimizing an MF by different criteria. As a result, we have formed a hybrid model consisting of heuristic search and GA. The results demonstrated the topicality of further research in this field.